(3GdcTa hGdHjGf aj JaSjQ GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s
(3ChdgG (B:s
(3jHOC HChd JaSjQ ShQI eQje s
(3BNQgG (B:s
(3jYedhf dg eG jTGA ef eMGQjH eSGLO heSGcf hbUhQ hGdeMQGH ebOe cd eLdS heSLO s
(3cJHJ GdGjGJ HNW cHjQ eTchds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B444s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs